Gender, linguistics, and leadership: A study of the language of coaches - Brooks, Jill (Working papers in Applied Linguistics and Linguistics at York, 2025)
This study focuses on the differences in the linguistic features of male and female coaches when leading men’s and women’s teams. Over the course of four weeks, three coaches were observed while coaching men’s and women’s team practices. Utterances were coded as either encouragement or criticism, and were also given a rating of either enthusiastic, calm, stern, or aggressive. In this paper, I compare the number of encouragement and criticism utterances from the male and female coaches toward each team, as well as compare the number of utterances made toward each team that were either enthusiastic, calm, stern, or aggressive. The results suggest that the coaches’ different linguistic styles are not innate but stem from conformity with language ideologies as a result of the two-cultures theory.